Isolation and Bacteriocin-Related Typing of Streptococcus dentisani - Conrads, Georg; Westenberger, Jacqueline; Lürkens, Martha; Abdelbary, Mohamed M. H. (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcus oralis subspecies dentisani is explored as an anti-cariogenic probiotic. Here, subjecting freshly stimulated saliva samples of 35 healthy volunteers, six epidemiologically unrelated and two related strains were isolated (prevalence around 20%) applying a newly developed three-step procedure. Furthermore, the probiotic strain S. dentisani 7746 (AB-Dentisanium®) was tested under a variety of environmental conditions for its inhibitory effect on six S. mutans, two S. sobrinus, 15 other oral or intestinal streptococci, 15 S. dentisani strains, and six representatives of other species including periodontopathogens. All except one S. mutans strains were inhibited by 7746 colonies or culture supernatant concentrate but only if either the test cell number was low or the producer or its bacteriocin concentration, respectively, was high. S. sanguinis OMI 332, S. salivarius OMI 315, S. parasanguinis OMI 335, S. vestibularis OMI 238 and the intestinal S. dysgalactiae OMI 339 were not inhibited, while the other 10 streptococcal strains (especially S. oralis OMI 334 and intestinal S. gallolyticus OMI 326) showed certain degree of inhibition. From the panel of other bacterial species only Aggregatibacter actinomycetemcomitans was slightly inhibited. With exception of OMI 285 and OMI 291 that possessed a 7746 bacteriocin-like gene cluster, all S. dentisani strains and especially type strain 7747T were strongly inhibited by 7746. In conclusion, probiotic strain 7746 might antagonize initiation and progression of dental caries by reducing S. mutans if not too abundant. S. dentisani strains inhibit each other, but strains with similar bacteriocin-related gene clusters, including immunity genes, are able to co-exist due to cross-resistance. In addition, development of resistance and adaptation to 7746-bacteriocins was observed during our study and needs attention. Hence, mechanisms underlying such processes need to be further investigated using omics-approaches. On the manufacturing level, probiotic strains should be continuously tested for function. Further clinical studies investigating inhibition of S. mutans by AB-Dentisanium® are required that should also monitor the impact on the oral microbiome composition including resident S. dentisani strains.